2013
DOI: 10.1016/j.curtheres.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Propofol and Ketamine-Propofol Mixture (Ketofol) on Laryngeal Tube-Suction II Conditions and Hemodynamics: A Randomized, Prospective, Double-Blind Trial

Abstract: ObjectiveThe aim of our study is to compare the effect of ketamine–propofol mixture (ketofol) and propofol on the laryngeal tube-Suction II (LTS II) insertion conditions and hemodynamics.MethodsEighty American Society of Anesthesiologists class 1 and 2 patients were divided into 2 random groups to receive either 1 µg/kg remifentanil and propofol 2 mg/kg in Group P (n = 40), or 1 µg/kg remifentanil and ketofol (using a 1:1 single syringe mixture of 5 mg/mL ketamine and 5 mg/mL propofol) in Group K (n = 40) befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…They showed significant results with p<0.05 with better insertion of laryngeal tube with minimal adverse airway responses and complications under ketofol (Group K ) induction as compared to propofol (Group P). 18 Goel S. also showed better insertion of LMA in Group PK (ketofol) and Group PM (propofol+midazolam) than in Group P (propofol) 19 which is also confirmed in our study.…”
Section: Discussionsupporting
confidence: 87%
“…They showed significant results with p<0.05 with better insertion of laryngeal tube with minimal adverse airway responses and complications under ketofol (Group K ) induction as compared to propofol (Group P). 18 Goel S. also showed better insertion of LMA in Group PK (ketofol) and Group PM (propofol+midazolam) than in Group P (propofol) 19 which is also confirmed in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Another study by Ghatak et al showed that addition of ketamine with propofol provides hemodynamic stability in children premedicated using clonidine for insertion of laryngeal mask airway (LMA) ( 21 ). However, Ozgul et al showed that ketamine-propofol combination provided minimal hemodynamic changes during insertion of laryngeal tube-suction ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to low cardiovascular side effect profile, ketamine is widely used as a combination agent in anesthetic procedures. However, it might delay postoperative recovery [3][4][5][6]. Depending on these previous literature, we hypothesized that using ketamine-propofol combination for colonoscopy procedures might result in shorter sedation achievement duration, lower hemodynamic and respiratory complication rates and less side effects.…”
Section: Introductionmentioning
confidence: 97%